Online Teacher Work to Support Self-Regulation of Learning in Students with Disabilities at a Fully Online State Virtual School - Rice, Mary Frances; Carter, Jr., Richard Allen (Online Learning, 2016)
Students with disabilities represent a growing number of learners receiving education in K-12 fully online learning programs. They are, unfortunately, also a large segment of the online learning population who are not experiencing success in these environments. In response, scholars have recommended increasing instruction in self-regulation skills for these students, but whether teachers are able to promote self-regulation as part of their instruction and how they will do so remains unknown. The purpose of this qualitative study was to examine how practicing teachers provided self-regulation strategies to students with disabilities in a fully online learning environment. In this context, the teachers intended to offer self-regulation strategies to students, but they were largely unable to do so. This work has the potential to influence professional development programs for online teachers in the hopes that students with disabilities will be able to learn self-regulation strategies and ultimately be more successful.